First evidence that deep-sea animals are ingesting microplastics.
Collaborative research funded by the ERC's CACH project has announced the first real evidence that deep-sea animals are ingesting microplastics that are finding their way into the world's oceans. This comes at a poignant moment as several governments are considering a ban on plastic microbeads, most often found in toiletries and cleaning products.